Research and Application of Ga-Based Liquid Metals in Catalysis - Yu Zhang; Ying Xin; Qingshan Zhao (Nanomaterials)
In recent years, Ga-based liquid metals have emerged as a prominent research focus in catalysis, owing to their unique properties, including fluidity, low melting point, high thermal and electrical conductivity, and tunable surface characteristics. This review summarizes the synthesis strategies for Ga-based liquid metal catalysts, with a focus on recent advances in their applications across electrocatalysis, thermal catalysis, photocatalysis, and related fields. In electrocatalysis, these catalysts exhibit potential for reactions such as electrocatalytic CO2 reduction, electrocatalytic ammonia synthesis, electrocatalytic hydrogen production, and the electrocatalytic oxidation of alcohols. As to thermal catalysis, these catalysts are employed in processes such as alkane dehydrogenation, selective hydrogenation, thermocatalytic CO2 reduction, thermocatalytic ammonia synthesis, and thermocatalytic plastic degradation. In photocatalysis, they can be used in other photocatalytic reactions such as organic matter degradation and overall water splitting. Furthermore, Ga-based liquid metal catalysts also exhibit distinct advantages in catalytic reactions within battery systems and mechano-driven catalysis, offering innovative concepts and technical pathways for developing novel catalytic systems. Finally, this review discusses the current challenges and future prospects in Ga-based liquid metal catalysis.